Résistances de l’anecdote : Brantôme et la dissidence narrative - Anne Duprat (Les Dossiers du GRIHL)
Pierre de Bourdeille, abbé of Brantôme, celebrated in his Memoires (ca. 1595) more than he deplored the effect of the religious and civil wars that did set off the exploits as well as the minor deeds of the great captains and noblemen of the time (1563-1582), through the part they publically played in the feuds of the princes they served, or in their private duels and quarrels of honour. This study will show that the aesthetic function bestowed by Brantôme to the composition of the « mémoires d’épée » could also shed light upon the political meaning of the detached attitude he adopts towards dissent and dissidence in his narratives of war and conflict.